PENERAPAN STRATEGI PENGAJARAN KETERAMPILAN BERBICARA DI MTsN 1 KOTA PADANG - Supiana Wulandari; Emidar (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
The implementation of speaking skills teaching strategies at MTsN 1 Padang City includes seven teaching components consisting of students, teachers, objectives, materials, strategies, media, and evaluation in learning which are mutually integrated and have an influence on the process of implementing teaching strategies. (a) students in speaking learning are active, creative and critical thinking learning subjects during the implementation of speaking skills teaching strategies, (b) teachers in the Merdeka curriculum as facilitators, mentors, and learning designers, (c) the objectives of teaching speaking skills are taken from the indicators of each learning objective of the speaking and presenting elements, (d) the teaching material for speaking skills is in the form of poetry texts that are in accordance with the theme and development level of grade VIII students, (e) the teaching strategy for speaking skills used by cooperative learning teachers is in the form of group discussions and presentations using video media as direct objects of student understanding, (f) the teaching media for speaking skills is visual media in the form of poetry reading videos, LKPD, and Indonesian language LKS, (g) the evaluation of teaching speaking skills is an evaluation of student performance in assessing poetry declamation using an assessment rubric consisting of aspects of indicators related to learning outcomes (CP) of the speaking and presenting elements. The implementation of this strategy uses a cooperative learning approach that is effective in improving students' understanding of the material, especially in analyzing poetry. Based on the results of this study, it can be concluded that the implementation of the speaking skills teaching strategy at MTsN 1 Padang City has been categorized as good. This can be seen from the seven teaching components that support its implementation. Although not all students are able to achieve good minimum completion criteria.